Improving the efficiency of exciplex based OLEDs by controlling the different configurations of the donor. Issue 2 (15th December 2020) - Zhang, Ning; Zheng, Caijun; Chen, Zhipeng; Zhao, Juewen; Zhang, Ming; Yang, Haoyu; He, Zeyu; Du, Xiaoyang; Tao, Silu
Abstract : Two new D–A–D-type donor materials with different molecular conformations, 10, 10′-(pyridine-2, 4-diyl)bis(9, 9-dimethyl-9, 10-dihydroacridine) and 10, 10′-(pyrimidine-2, 4-diyl)bis(9, 9-dimethyl-9, 10-dihydroacridine), were synthesized and applied in exciplex-based OLEDs. Abstract : Two D–A–D type donor materials, 10, 10′-(pyridine-2, 4-diyl)bis(9, 9-dimethyl-9, 10-dihydroacridine) (Pra-2DMAC) with vertical molecular conformation and 10, 10′-(pyrimidine-2, 4-diyl)bis(9, 9-dimethyl-9, 10-dihydroacridine) (Prm-2DMAC) with near-planar molecular conformation, were designed and synthesized in order to develop the performance of exciplex based OLEDs. Pra-2DMAC shows a better performance than Prm-2DMAC, due to its vertical configuration, which has a beneficial effect on exciplex emission because the separated HOMO and LUMO in donor facilitates the intramolecular charge transfer (ICT) and reverse intersystem crossing (RISC) process at the excited state. An exciplex device with a simple structure based on Pra-2DMAC shows a high maximum external quantum efficiency (EQE) of 15.0% (13.9% at 1000 cd m −2 ), low turn-on voltage of 2.4 V, and stable electroluminescence spectrum of nearly constant CIE coordinate. The better performance of Pra-2DMAC demonstrates the superiority of the donor with vertical configurations in an exciplex system. To our knowledge, this is the first work to study exciplex based OLEDs using dual configuration donor materials.